Μηχανική συμπεριφορά διαβρωμένων χαλύβων οπλισμού σκυροδέματος - Καρίττεβλη, Παναγιώτα (Τμήμα Πολιτικών Μηχανικών και Μηχανικών Γεωπληροφορικής, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2015)
Steel is currently one of the main structural materials because it can be used in various fields of the building construction such as the metallic structures as well as reinforcement in the concrete. Although this composite material performs exceptionally well, it has been noted that during the life span of reinforced concrete structures, a gradual damage accumulation takes place and it is called corrosion of steel reinforcement. The problems of corrosion in structures in northern climates are accentuated by the use of salt for melting snow. Significant risk from the presence of salt there is in coastal structures and this is why the phenomenon on the island, is very common, mainly because of our location and climatic conditions. This phenomenon appears most often in coastal areas and so most test are close to the shoreline. From a purely theoretical point of view it is possible to design and product concrete so that the integrated steel does not corrode. Although, in practice, either due to manufacturing requirements or due to deviations from manufacturing specifications, corrosion generated and could even result in disclosure of steel. Without recognition and attention in time can become fatal for construction. For these reasons spot controls take place (not-destructive) for determining the erosion size. During the preparation of this thesis, a study of the mechanical behavior of concrete reinforcing steels in conditions of laboratory accelerated corrosion through the research program «STEELCOR» carried out by the Cyprus University of Technology. Outcomes and suggestions from the laboratory works are presented.
Keywords: Steel; Reinforced concrete; Corrosion; Χάλυβας; Οπλισμένο σκυρόδεμα; Διάβρωση